First Report of Phialocephala bamuru Causing Root Rot on Hard Fescue (Festuca brevipila) in the United States - Fardella, Patrick (Plant disease, 2024)
Turfgrasses are susceptible to a wide variety of ectotrophic root-infecting (ERI) fungi that cause root rot (Tredway et al., 2023). Among the root rot diseases, fairway patch, caused by Phialocephala bamuru P.T.W. Wong & C. Dong sp. nov., was recently identified and characterized in Australia infecting bermudagrass (Cynodon dactylon) and kikuyu (Pennisetum clandestinum) grass (Wong et al., 2015). Symptoms begin as small, 5-10 cm diameter patches of yellowed turf that may coalesce into larger areas of diseased grass. A characteristic sign of fairway patch is roots colonized by dark brown to black, ectotrophic mycelium. In June 2020, many tan colored, irregular-shaped patches ranging from 10-30 cm in diameter developed on a hard fescue (Festuca brevipila) cultivar 'Beacon' turfgrass field in North Brunswick, New Jersey, USA. The centers of these patches later died and became sunken or filled in partially by recovering hard fescue. The patches grew into tan irregular-shaped rings with diameters up to 3 m by Aug 2023. Symptoms were indicative of a root disease. Five 'Beacon' hard fescue soil cores at the interface of the symptomatic and non-symptomatic area were sampled in Aug 2023. Root and crown samples were observed under a dissecting microscope and dark ectotrophic hyphae were observed on both. Roots with visible ectotrophic mycelium were removed, rinsed in sterile water three times, cut into 5 mm pieces, and plated onto 10% potato dextrose agar amended with streptomycin and gentamicin at 100 mg/L (PDA+). The plates were incubated at 25°C in the dark for 5 days. The most abundant colonies being characteristic long, septate hyphae that were hyaline at the edge and dark brown to black in the center and resembled the fungus described in Wong et al., 2015. These colonies were subcultured onto PDA+ medium and selected for molecular identification. Other less abundant colonies could be identified using morphology after subcultured and had no record being pathogenic to turfgrass. To confirm the isolate's identity, its internal transcribed spacer (ITS) region was amplified in PCR using the ITS1F/ITS4 primers (Bellemain et al., 2010). The amplicon was then sequenced with both ITS1 and ITS4 primers by Sanger sequencing. Sequences were assembled (GenBank #PP000819). The consensus sequence was then BLASTn analyzed with default settings, and the result showed 99.64% sequence identity with P. bamuru (GenBank #MG195534.1). Koch's postulate was conducted in an environmentally controlled growth chamber. Six healthy 'Beacon' hard fescue plugs were sampled from the field. Three of the six plugs (treatment) were each inoculated with P. bamuru by placing 20 g of P. bamuru colonized millets beneath and around the plug before filling the pots with sand. The other three plugs (control) received the same treatment except the P. bamuru colonized millets were autoclaved. The pots were incubated in the growth chamber with a 16 h light period and 25/20°C day/night temperatures. Symptoms resembling those observed in the field appeared on the treatment pots after 21 days of incubation while the control pots remained healthy. The roots from the treatment pots were examined under the dissecting microscope to confirm the colonization of P. bamuru on the roots, and P. bamuru was reisolated and confirmed using the aforementioned morphological traits and molecular assays (GenBank #PP000820). This is the first report of a turfgrass root rot disease caused by P. bamuru in the United States. Further epidemiological, disease ecological, and pathogen biological studies are required to clarify the importance of this disease in the United States and establish proper disease containment or control measures